Efficient computation of Cantor's division polynomials of hyperelliptic curves over finite fields. (July 2023) - Eid, Elie
Abstract: Let p be an odd prime number. We propose an algorithm for computing rational representations of isogenies between Jacobians of hyperelliptic curves via p -adic differential equations with a sharp analysis of the loss of precision. Consequently, after having possibly lifted the problem in the p -adics, we derive fast algorithms for computing explicitly Cantor's division polynomials of hyperelliptic curves defined over finite fields.